A pessoa idosa: uma análise da aplicabilidade do estatuto do idoso nas ações de cuidados pastorais - Castro, Maria da Graça Borges de Moraes (2015)
The Brazilian population is increasingly older. Besides this, the demographic perspectives point to an increasingly accentuated aging of the population with real possibilities of becoming a country with an elderly population mass greater than the active one in some decades. Since the country is constituted by an elderly population contingency it is quite comprehensible that changes in the way of understanding the significance of being old and of aging begin to appear and demand greater levels of reflection. For this, we committed ourselves to carry out a philosophical-theological reflection based on the reality of the elderly person through the concept of care. We take such a concept from the work of Martin Heidegger and from Leonardo Boff who transfer it to the realm of knowledge as an ethical-social competency and assume creation itself as otherness. This work is organized in three chapters, the first being dedicated to the theme of the elderly person and the process of aging; the second is related to the concept of care in the works of Heidegger, Boff and Michel Foucault; and the third deals with a theological-curative reading of the Statute of the Elderly.